2022
DOI: 10.1149/10701.3207ecst
|View full text |Cite
|
Sign up to set email alerts
|

Design of Machine Learning Based Model to Predict Students Academic Performance

Abstract: Artificial intelligence relies heavily on machine learning. Classifying and forecasting outcomes may be done using machine learning. Student performance assessment demonstrates how much effort educational institutions should put in to help the underachieving or average student. Using EDM models is important because they use previous student data to predict future student performance. To help students and teachers improve their performance, educational institutions use a range of ways to gather information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Measuring and predicting students’ performance is a great way for educational institutes to improve the curriculum or the school’s studying atmosphere. In recent studies, among the machine learning algorithms, support vector machine (SVM) [ 28 ] has been shown to outperform other machine learning algorithms in terms of predicting student outcomes. In most studies, people generally opt to investigate with SVM techniques, which can be used extensively in classification problems.…”
Section: Related Workmentioning
confidence: 99%
“…Measuring and predicting students’ performance is a great way for educational institutes to improve the curriculum or the school’s studying atmosphere. In recent studies, among the machine learning algorithms, support vector machine (SVM) [ 28 ] has been shown to outperform other machine learning algorithms in terms of predicting student outcomes. In most studies, people generally opt to investigate with SVM techniques, which can be used extensively in classification problems.…”
Section: Related Workmentioning
confidence: 99%
“…Computers, videos, tape recorders, Powerpoint presentations, and mobile phones are only some of the technological tools included in the English language education system at all levels. Some research has shown that using vlogs as a tool for language learning may help college students become better writers (Rafique et al, 2021, Veluri et al, 2022, Arcinas, 2022. While this user-friendly technology has yet to catch on in the United States, many international instructors have included it in their classrooms and language education (Coombs et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This goal aims to provide inclusive and equitable education opportunities that enable all individuals, regardless of gender or socioeconomic background, to attain functional literacy and numeracy skills comparable to those gained after completing basic education. While progress has been made in reducing global illiteracy rates, there is still much work to be done to ensure that everyone has access to the education they need for a sustainable future (Arcinas, 2022, Amparo et al, 2022, Afable et al, 2022. As access to education is a crucial component of sustainable development, the study explores the use of Viber as a support tool in enhancing students' writing skills and online language learning engagement.…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge that students engaged in writing during the pandemic has been a great challenge since the language is not their primary language. Due to uncontrollable circumstances, teachers cannot find an appropriate website or social media to hold their learners' engagement (Abbaset al, 2019;Bhagat & Kim, 2020, Arcinas, 2022, Rad et al, 2022. A study made by Altınmakas and Bayyurt (2019) in the school's Division of Laoag City, specifically Senior High School, showed that organization, inappropriate words and poor word utilization in terms of vocabulary and choice of words, poor sentence structure regarding language usage, use of the first-person pronoun in terms of formality and objectivity, and absence of citations when referencing are all issues that students face when writing academic essays (Fathi et al, 2019;Mercer, 2019).…”
Section: Introductionmentioning
confidence: 99%